Efficacy and safety of tebentafusp in patients with metastatic uveal melanoma: A systematic review and meta-analysis - Yating Dian; Yihuang Liu; Furong Zeng; Yuming Sun; Guangtong Deng (Taylor & Francis Group, 2024)
Patients with metastatic uveal melanoma (mUM) have a poor prognosis, and few appropriate medications are available. Tebentafusp is approved by the Food and Drug Administration for mUM recently. However, the real efficacy and safety of tebentafusp are still unclear. We searched PubMed, Embase, and Cochrane Library from inception to March 20, 2024. The research was reported based on the preferred reporting items for systematic reviews and meta-analysis guidelines. We used random effects models to aggregate data on the response rates and adverse events of tebentafusp therapy. Six studies met the inclusion criteria with a total sample of 589 participants. The pooled objective response rate was 0.08 (95% CI: 0.05-0.12), and pooled disease control rate was 0.51 (95% CI: 0.44-0.57). The overall incidence was 0.99 (95% CI: 0.95-1.00) for any grade adverse events, 0.50 (95% CI: 0.41-0.59) for grade 3-4 adverse events, and 0.01 (95% CI: 0-0.03) for discontinuation due to adverse events. Tebentafusp exhibits promising treatment outcomes for mUM patients. Although accompanied with a common occurrence of adverse events, which can typically be managed and controlled. Future research is necessary for substantiating these findings and refining guidelines for management of mUM.